PEMBERDAYAAN KADER DALAM PEMBUATAN MAKANAN PENDAMPING ASI (MPASI) BERBAHAN LOKAL - Sari, Novia; Sari, Sherly Mariance (LPPM Institut Pendidikan Nusantara Global, 2022)
Complementary food for ASI is food given to infants/children in addition to breast milk to meet their nutritional needs. Complementary foods are started to be given to babies aged 6 months, because the nutritional needs to support their growth and development are still lacking if only breast milk. Breast milk only meets the needs of about 60% -70% of a baby's needs after the age of 6 months. Meanwhile, 30% -40% must be met from complementary foods. Therefore, it is very important to educate the community through empowering cadres as an extension in providing assistance to mothers who have toddlers in providing additional food to babies. Community service activities were carried out in the working area of ​​the Megang Health Center on November 12, 2022 with 15 toddler cadres as respondents. The stages of the activities carried out included making leaflets, providing counseling about complementary foods and demonstrating the preparation of complementary foods with a balanced menu (carbohydrates, animal protein, vegetable protein, vegetables and fat) using local ingredients. The results of community service, after conducting knowledge counseling for cadres, the average is 78% in the good category. Then after the demonstration, the cadres were able to make a well-filtered MPASI menu. So it is recommended that the involvement of cadres in empowering mothers who have toddlers in making MPASI with a balanced menu through the use of local ingredients.